Neonatal Outcomes After the Obstetric Near-miss Events Uterine Rupture, Abnormally Invasive Placenta and Emergency Peripartum Hysterectomy: Prospective Data From the 2009 to 2011 Finnish NOSS Study. Issue 4 (December 2016) - Jakobsson, M.; Tapper, A.M.; Palomäki, O.; Ojala, K.; Pallasmaa, N.; Ordén, M.R.; Gissler, M.
Abstract : ( Acta Obstet Gynecol Scand . 2015;94:1387–1394) The objective of this study was to assess fetal and neonatal outcomes in women with the obstetric near-miss complications of abnormally invasive placenta (AIP), uterine rupture, and emergency peripartum hysterectomy using the Finnish Nordic Obstetric Surveillance Study (NOSS) population.